2019
DOI: 10.1080/1828051x.2019.1621215
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a new feed block for the gut health and welfare of the weaning pig

Abstract: Pig weaning cause transient stress and reduction of feed intake and intestinal villi. Providing feed with solid texture could stimulate explorative interest, relieving weaning drawbacks and improving welfare. Feed blocks (0.8 kg each) were produced and 8 formulas were preliminarily tested for consumption on a pig farm (ingredients: wheat by-products, dried milk whey, calcium carbonate, oil, molasses). Feed consumption and growth within 3 days after weaning were assessed on penned litters fed the normal feed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Patoo et al (2014) found concentrate jaggery scum feed blocks acceptable for pigs. Trevisi et al (2019) developed three formula (using wheat by-products, dried milk whey, calcium carbonate, oil, molasses) of feed block preparation for pigs and observed not significant difference in growth and carcass quality than normal feeding. They observed that formulation with wheat middlings, cane molasses, milk whey and coconut oil increased the mucosal surface area of the intestinal villi by 7.9% (p<0.05) and the length of time the pigs slept (p<0.01).…”
Section: Acceptability Of Complete Feed Block In Pigsmentioning
confidence: 99%
“…Patoo et al (2014) found concentrate jaggery scum feed blocks acceptable for pigs. Trevisi et al (2019) developed three formula (using wheat by-products, dried milk whey, calcium carbonate, oil, molasses) of feed block preparation for pigs and observed not significant difference in growth and carcass quality than normal feeding. They observed that formulation with wheat middlings, cane molasses, milk whey and coconut oil increased the mucosal surface area of the intestinal villi by 7.9% (p<0.05) and the length of time the pigs slept (p<0.01).…”
Section: Acceptability Of Complete Feed Block In Pigsmentioning
confidence: 99%